PWE-028 Polyps seen but not removed during index colonoscopy: an unexplored inefficiency in endoscopy practice. (17th June 2017) - Beg, S; Jegatheeswaran, L; Sansone, S; ragunath, K
Abstract : Introduction: Colonoscopy offers the possibility of colorectal cancer prevention through the detection and removal of polyps. In the UK the Joint Advisory Group for endoscopy certifies endoscopists for independent practice once they are able to remove polyps of up to 20 mm in size. Where polyps are detected but not removed during the index colonoscopy, a repeat procedure is required. The aim of this study is to identify the proportion of polyps below the size of 20 mm which are not removed at the time of diagnosis. Method: A database review of all colonoscopies where at least one polyp was identified between 1 st January 2015 and 31 st December 2015 at Nottingham University Hospitals was performed. All polyps were categorised according to the reported size and the complexity as per the Size Morphology Site Access (SMSA) classification. Where polyps of 20 mm or below were not removed the patient's records and endoscopy reports were reviewed to establish the reasons for this and to determine the subsequent patient pathway. Results: During the 12 month study period 8632 colonoscopies were performed. A total of 4598 polyps were identified in 2426 patients. Polyps of 20 mm or less were diagnosed in 2345 patients, with subsequent polypectomy in 2066 (88%). Of the procedures where a polypectomy was not performed, 71 patients were on anticoagulant or antiplatelet therapy and 22 had reported poor bowel preparation with corroborative photo-documentation. Polypectomy was not performed in 186 patients, representing 8.2% of patients with polyps below 20 mm and with no contraindications to intervention. The reasons cited for this approach included; inadequate time available (n=4), procedure felt to be beyond the endoscopist's technical expertise (n=56) and no reason cited (n=126). The mean SMSA score of the non-removed polyps was 7.5 (level 2), denoting low to moderate complexity. As a result of the inappropriate non-removal of polyps 170 repeat endoscopies were required within the 12 month period. Conclusion: This study demonstrates that a significant proportion of small colorectal polyps are not removed at the time of diagnosis. This practice has implications to patients with the requirement of further bowel preparation, sedation and procedure associated risks, as well as to service costs. Disclosure of Interest: None Declared